Putting Voluntary, Charity, and Social Enterprise (VCSE) Organisations at the Heart of Research: Creating a Northern Ireland VCSE Research Directory - Spikol, Eric; Redican, Enya; McBride, Orla; Murphy, Jamie; Shevlin, Mark (International Journal of Population Data Science, 2026)
Introduction Voluntary, community, and social enterprise (VCSE) organisations provide vital public services, support, and information while promoting and sustaining community cohesion. These organisations should be at the centre of research as they are uniquely placed to identify critical evidence gaps and to realise the full potential of research findings. Objective A mapping exercise was undertaken to identify all VCSEs in Northern Ireland (NI), explore categories of organisational remit, identify key beneficiary and underserved populations, and to create a searchable database of NI VCSEs. Methods Publicly available descriptive data provided by NI VCSEs were taken from not-for-profit sector administrative and regulatory organisation websites, and were then cleaned, categorised, and centralised in a directory tool. Results In total, 40 primary remit categories and six unique secondary remit categories were identified, with N=17 categories covering distinct or specific beneficiary populations, N=3 having a non-human remit, and N=20 categories working on a community or general population level. Locational analysis showed the county-level distribution of VCSEs to be roughly proportional to the population percentages of each county. Conclusions Compiling and summarising the NI VCSE landscape has provided critical insights into trends within the sector and facilitated the creation of a centralised, accessible, and searchable directory of all VCSE organisations in NI the VCSE-Finder NI, a freely available tool intended to facilitate engagement and networking between researchers and VCSEs.